Spatial variability of the texture in a red-yellow ultisol under pasture and nature vegetation crop - Lima, Julião Soares de Souza; Sattler, Marcos Antonio; Xavier, Alexandre Cândido; de Oliveira, Rone Batista; Passos, Renato Ribeiro [UNESP]; Oliveira, Paulo César (My University, 2009)
The study of the spatial variability of soil attributes under different crop helps the study of changes due the management. This research was carried out to determine spatial variability the particle-size distribution, using of the classic statistic and geostatistics, of a soil cultivated with pasture and native vegetation. Soil samples were collected in the layer 0-0.20m, at the crossing points of a regular grid with 10m- intervals, summing up 64 samples points in each area. In the pasture area the fractions of coarse and total sand presented larger mean values in relation to the native vegetation, and negative correlation with the altitude of the points samples in the two areas. All of the fractions presented moderate to high spatial dependence in the two areas and with the defined still, with exception of the fine sand and the silt in the pasture. Much of this variability occurs as a function of water erosion.
Variabilidade espacial da textura de um Argissolo Vermelho Amarelo sob cultivo de pastagem e vegetação nativa
Keywords: Kriging; Soil management; Spatial distribution